Installed Base and Compatibility: Innovation, Product Preannouncements, and Predation - Farrell, Joseph; Saloner, Garth (American Economic Review, 1986)
A good is often more valuable to any user, the more others use compatible goods. We show that this effect may inhibit innovation. If an installed base exists and transition to a new standard must be gradual, early adopters bear a disproportionate share of transient incompatibility costs. This can cause "excess inertia." The installed base, however, is "stranded" if the new standard is adopted: this may create "excess momentum." These dynamic effects have strategic implications.